Modernisasi UMKM: Merancang Tahapan Implementasi Berbasis Sistem untuk Mengatasi Ancaman Siklus Persediaan (Studi Kasus pada UMKM X): Studi Kasus pada UMKM X - Santoso, Nathalia; Sutomo, Felisia (Politeknik Ganesha Medan, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the economic recovery of Indonesia by contributing significantly 60% of Indonesia's GDP and employing 96% of the national workforce. However, internal challenges arise as employee-instigated theft and embezzlement resurface due to a lack of security knowledge among MSME owners. This knowledge gap poses a growing risk as MSMEs become more susceptible to fraud, particularly in relation to inventory cycles. MSME X has been chosen as the subject of this research due to its limited understanding of the importance of internal control systems and the non-execution of an accounting information system, notably in the manufacturing sector, where theft risks are heightened. The inventory cycle is closely linked to the sales, purchasing, and production cycles due to the involvement of raw materials, semi-finished goods, and finished goods. The study adopts applied research methods, utilizing both primary (interviews and observations) and secondary data (literature studies). Findings reveal inadequate control activities in MSME X, exacerbated by the absence of functional separation and proper documentation for inventory transactions. Recommendations include a five-stage implementation plan, starting with flowchart creation, CCTV installation, and personnel recruitment. The middle stage involves additional recruitment and transitioning to a digital accounting information system for process integration. The final stage integrates the accounting information system with external parties. Performance evaluations will be conducted at each stage to assess the effectiveness of the accounting information system in minimizing risks